1982
DOI: 10.1007/bf01949417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sphingolipids on erythroblastic maturation in the mouse

Abstract: The changes effected by injection of an extract of phospholipids obtained from the plasma of normal human donors (PLE) or an emulsion of commercially available sphingolipids on erythropoiesis in the mouse were studied. The parameters followed were 59Fe uptake by the erythroid tissue and the number of circulating reticulocytes. It was found that in the 12--24-h period following administration of PLE or purified sphingomyelin a significant increase in 59Fe uptake by circulating RBC an by their hemic fraction tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Consistent with our data, studies by Clayton et al showed an induction of erythropoiesis by sphingomyelin in bone marrow of rats in vitro (29). Moreover, Scaro and colleagues observed an increase of circulating reticulocytes after injecting mice with purified sphingomyelin in vivo (25).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our data, studies by Clayton et al showed an induction of erythropoiesis by sphingomyelin in bone marrow of rats in vitro (29). Moreover, Scaro and colleagues observed an increase of circulating reticulocytes after injecting mice with purified sphingomyelin in vivo (25).…”
Section: Discussionsupporting
confidence: 91%
“…Next, we determined sphingomyelin levels in bone marrow of Ac WT and Ac KO mice. Sphingomyelin is generated from ceramide by the activity of sphingomyelin synthases and has been shown to increase the number of reticulocytes in mice (25). While sphingomyelin levels were decreased in bone marrow of Ac KO mice compared to Ac WT mice at day 0 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of SM was further corroborated in 1986 by Scaro et al, when an extract of phospholipids from human plasma, as well as purified SM, were injected into mice. This resulted in an increased number of reticulocytes in circulation, suggestive of an increase in erythropoietic turnover [72]. Furthermore, Dallalio et al showed that ceramide inhibited CFU-E colony formation while S1P reversed this inhibition [73].…”
Section: Sphingolipids In Erythroid Differentiation and Erythrocytesmentioning
confidence: 99%
“…Next, we determined sphingomyelin, sphingosine, and S1P levels in bone marrow of Ac WT and Ac KO mice. Sphingomyelin is generated from ceramide by the activity of sphingomyelin synthases and has been shown to increase the number of reticulocytes in mice ( Scaro et al, 1982 ). While sphingomyelin levels were decreased in bone marrow of Ac KO mice compared to Ac WT mice on day 0 ( Figure 5D , left panel), they were significantly enhanced on day 7 in the presence ( Figure 5D , right panel) and absence ( Figure 5—figure supplement 1 ) of the infection, correlating with increasing reticulocyte frequencies observed before.…”
Section: Resultsmentioning
confidence: 99%